The effect of seasoning with herbs on the nutritional, safety and sensory properties of reduced-sodium fermented Cobrançosa cv. table olives - Pires-Cabral, Paula (2019)
This study aimed at evaluating the effectiveness of seasoning Cobrancosa table olives in a brine with aromatic ingredients, in order to mask the bitter taste given by KCl when added to reduced-sodium fermentation brines. Olives were fermented in two different salt combinations: Brine A, containing 8% NaCl and, Brine B, a reduced-sodium brine, containing 4% NaCl + 4% KCl. After the fermentation the olives were immersed in seasoning brines with NaCl (2%) and the aromatic herbs (thyme, oregano and calamintha), garlic and lemon. At the end of the fermentation and two weeks after seasoning, the physicochemical, nutritional, organoleptic, and microbiological parameters, were determined. The olives fermented in the reduced-sodium brines had half the sodium concentration, higher potassium and calcium content, a lower caloric level, but were considered, by a sensorial panel, more bitter than olives fermented in NaCl brine. Seasoned table olives, previously fermented in Brine A and Brine B, had no significant differences in the amounts of protein (1.23% or 1.11%), carbohydrates (1.0% or 0.66%), fat (20.0% or 20.5%) and dietary fiber (3.4% or 3.6%). Regarding mineral contents, the sodium-reduced fermented olives, presented one third of sodium, seven times more potassium and three times more calcium than the traditional olives fermented in 8% NaCl. Additionally, according to the panelists' evaluation, seasoning the olives fermented in 4% NaCl + 4% KCl, resulted in a decrease in bitterness and an improvement in the overall evaluation and flavor. Escherichia coli and Salmonella were not found in the olives produced.